Developing a Tutoring Program for an interdisciplinary university task - Araitz Uskola Ibarluzea; José Mª Madariaga Orbea; Ana Arribillaga Iriarte; Gurutze Maguregi González; Ainara Romero Andonegui; Mª Dolores Fernández Alonso (Universitat Politècnica de València, 2015)
The teacher degrees at the Teaching College of Bilbao from Basque Country University UPV/EHU have a four-monthly modular structure. In each module students have to perform an interdisciplinary task that includes all subjects of the module. This paper presents the proposal that a team of six teachers from different fields of knowledge has designed to address the tutoring of that task. The tutoring has been carried out with students that are studying the second module of the Primary Education Grade, which belongs to the first year of the degree. In this module the task consists in working in groups following the PBL methodology (Problem-Based Learning). The objectives were to redesign the  initial  scenario,  design  a  plan  of tutoring for students, and socialize results among other teachers of the module. The initial scenario has been written up taking into account the objectives and the activities of the Modular Interdisciplinary Task (TIM). The tutoring plan, organized in several sessions, includes the objectives to be achieved, tasks to be performed, the methodology -which is based on cooperative learning-, and the assessment. Besides, the results have been shared with other teachers of the module so that the results of this work have effect in the practice  of  all  teachers.  Finally,  and  in order to determine the satisfaction level of students about the changes proposed, a questionnaire has been designed, which has been answered by 61 students.